Predictors of diffuse myocardial fibrosis in HIV infected persons: A multiparametric cardiovascular magnetic resonance study - Saad, Hadil (Department of Medicine, 2020)
With the advent of effective antiretroviral therapy (ART), human immunodeficiency virus (HIV) is now a chronic disease. With increasing survival, cardiovascular disease (CVD) in people living with HIV is increasing in the ART era, with a changing epidemiology that is now largely characterised by diastolic dysfunction. Our hypothesis was that ART would be associated with regression of myocardial fibrosis in HIV. Myocardial fibrosis is associated with an unfavourable outcome in many different clinical settings. In this study, we used cardiovascular magnetic resonance (CMR) measurements of extracellular volume fraction (ECV) and tissue characterisation to assess diffuse myocardial fibrosis and determine the effect of ART use on diffuse myocardial fibrosis in HIV infected individuals on ART compared to untreated HIV infected persons. Forty-four asymptomatic individuals with no known CVD who were HIV infected were included and classified into two groups: 25 on ART for >1 year (60% male, mean age 40 ± 9 years) and 19 ART-naïve (37% male; mean age 36 ± 8 years). All patients underwent CMR on a 3T Siemens Skyra scanner. Imaging included cine, T2 weighted (STIR), native T1 and T2 mapping, late gadolinium imaging (LGE) and ECV imaging. HIV infected patients not on ART had a median time from diagnosis to entry in the study of 9 months. Treated patients had been stable on ART for over 12 months. There was no difference in left ventricular volumes, mass and function between treated and untreated HIV-infected patients. We found that, while elevated in both groups, the native T1 values were lower in the treated group compared to untreated patients. Again, while elevated in both groups, the ECV was slightly lower in the treated group, this did not reach statistical significance. There was no correlation between native T1 value or ECV with either disease duration or nadir CD4 count. There was no difference in left ventricular volumes, mass and function between treated and untreated HIV-infected patients. We found that, while elevated in both groups, the native T1 values were lower in the treated group compared to untreated patients. Again, while elevated in both groups, the ECV was slightly lower in the treated group, this did not reach statistical significance. There was no correlation between native or ECV with either disease duration or nadir CD4 count. We conclude that in patients with HIV, diffuse myocardial fibrosis provides valuable insights into the pathophysiology of HIV associated CVD and mechanism of diastolic dysfunction. Importantly, in this study, with a short lead period on ART, ART was associated with regression of diffuse myocardial fibrosis, as assessed by native T1, but not by ECV. Larger prospective studies are needed with longer follow-up to assess the role of CMR in both risk stratification and in tracking disease progression in HIV.